2017
DOI: 10.1186/s12864-016-3413-8
|View full text |Cite
|
Sign up to set email alerts
|

Cecal MicroRNAome response to Salmonella enterica serovar Enteritidis infection in White Leghorn Layer

Abstract: Background Salmonella enterica serovar Enteritidis (SE) is a food-borne pathogen and of great threat to human health through consuming the contaminated poultry products. MicroRNAs (miRNAs) play an important role in different biological activities and have been shown to regulate the innate immunity in the bacterial infection. The objective of this study is to identify miRNAs associated with SE infection in laying chicken cecum.ResultsAverage number of reads of three libraries constructed from infected and non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 73 publications
4
29
0
Order By: Relevance
“…Another binding site enrichment analysis of miRNAs responsible for deregulated mRNAs in peripheral blood suggested that miR-143 and miR-26 might be involved in the initiation and progression of Salmonella infection in pigs 47 . In addition, miRNAs may also modulate the innate immunity involving miRNAs to S. enteritidis infection in laying chicken ceca 48 . Thus, these deregulated miRNAs may be functionally important for manipulating Salmonella-induced inflammation.…”
Section: Mirnas Affected By Bacterial Infectionsmentioning
confidence: 99%
“…Another binding site enrichment analysis of miRNAs responsible for deregulated mRNAs in peripheral blood suggested that miR-143 and miR-26 might be involved in the initiation and progression of Salmonella infection in pigs 47 . In addition, miRNAs may also modulate the innate immunity involving miRNAs to S. enteritidis infection in laying chicken ceca 48 . Thus, these deregulated miRNAs may be functionally important for manipulating Salmonella-induced inflammation.…”
Section: Mirnas Affected By Bacterial Infectionsmentioning
confidence: 99%
“…The role of miRNA in response to bacterial infection has also been investigated in chickens. Several miRNAs (gga-miR-125b-5p, gga-miR-34a-5p, gga-miR-1416-5p, and gga-miR-166) associated with SE infection were identified recently in laying chicken cecum by next generation sequencing (Wu et al, 2017 ). A novel splenic miRNA, gga-miR-429, involved in the host response to Avian pathogenic Escherichia coli (APEC) was also detected by deep sequencing (Jia et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The circadian rhythm associated genes were not enriched following SE infection [20]. While, the circadian rhythmassociated circRNAs and miRNAs were signi cantly triggered by SE inoculation [24,55]. The methylation variation of rhythmic process-related genes was triggered in chicken following SE inoculation in the current study.…”
Section: Discussionmentioning
confidence: 49%
“…Genome-wide DNA methylation can uncover epigenetic modi cation changed with animal development, evolution and environmental adaptation [21][22][23][24][25]. DNA methylation has been reported in many species such as human [26], bovine [21], soybean [27], rat [28], rice [29] and chicken [30].…”
Section: Introductionmentioning
confidence: 99%